In situ detection of mutated hepatitis B virus in microdissected, formalinfixed liver tissues from patients with chronic hepatitis B - Kojima, Naohiko; Horiike, Norio; Michitaka, Kojiro; Onji, Morikazu (Journal of hepatology, 1999)
Background/Aims: Hepatitis B virus (HBV) quasispecies have been detected in patients with chronic hepatitis B. In order to elucidate the relationship between HBV mutation and liver cell necrosis in situ, we analyzed sublobule-sized specimens microdissected from formalin-fixed paraffin-embedded liver biopsy tissues taken from patients with chronic hepatitis B. Methods: The subjects were 20 patients with chronic hepatitis B. We extracted HBV-DNA from two sublobular regions of HBV-infected liver biopsy tissue, those with the most severe and the mildest hepatitis activity, demonstrated microscopically. The DNA coding sequence of the precore-core region of HBV was determined by amplifying the DNA by the polymerase chain reaction, followed by direct sequencing. Results: In all seven patients with minimal to mild hepatitis activity, but only 4 of 13 with moderate to severe activity, the amino acid sequence of the precore-core region of HBV obtained from the region with the most severe hepatitis activity showed over 99% homology with the corresponding sequence of HBV obtained from region with the mildest hepatitis activity ( p<0.05). Conclusion: The differences between intrahepatic HBVs observed in patients with highly active hepatitis suggest that exacerbation of hepatitis in vivo is related to the appearance of variants in the precore-core region of HBV.